Integrated business information systems : a holistic view of the linked business process chain ERP-SCM-CRM-BI-Big Data /: a holistic view of the linked business process chain ERP-SCM-CRM-BI-Big Data. ([2020]) - Gronwald, Klaus-Dieter
No abstract available